Job satisfaction of agency-hired workers in selected fast food establishments in Metro Manila - Galang, Monica Camille V. 1994-; Serrano, Melisa R.; Certeza, Ramon A.; Ofreneo, Rene; Velasco, Benjamin B.; University of the Philippines Diliman. School of Labor and Industrial Relations (Quezon City : School of Labor and Industrial Relations, University of the Philippines Diliman, 2022.)
This study sought to determine the overall level of job satisfaction of agency-hired workers in selected fast-food establishments in Metro Manila before the COVID-19 pandemic. It also aimed to identify and analyze the factors that influence job satisfaction of agency-hired workers and differentiate the job satisfaction level between agency-hired fast-food workers and directly hired fast-food workers. Using a mixed-method technique, which included an in-face survey of 128 fast-food workers (91 agency workers and 37 directly-hired workers) in eight branches of a big fast-food chain in Metro Manila and online (via Zoom) key information interviews, the study found that agency-hired workers in these establishments have an overall low job satisfaction rating. Four sets of factors, namely environmental factors (i.e. communication between superiors and subordinates, worker voice, how work s organized), strategic employee recognition factors (i.e. pay, fringe benefits, contingent rewards), individual factors (i.e. nature of work, operating conditions), and psychological well-being factors (i.e. HR programs, work time) influenced their perception and level of job satisfaction. Interestingly, the study also showed no significant differences between the level of job satisfaction of agency-hired and directly hired workers, which can be explained by these workers' unmet, albeit different, job aspirations and expectations. Nonetheless, agency-hired workers generally has a lower level of job satisfaction, specifically on the environmental factors (i.e. employee voice and representation and communication between superiors and subordinates). The findings of the study underscore the need to strengthen government policies on job security ans skills training and for staffing agencies to undertake HR programs for both area managers/coordinators and agency-hired workers.
Thesis (Master of Industrial Relations)--University of the Philippines Diliman
Includes bibliographical references (pages 140-149).
Keywords: Restaurants -- Employees -- Job satisfaction -- Philippines -- Metro Manila; Job satisfaction -- Philippines -- Metro Manila